Knowledge about COVID-19 and vaccine acceptability among priority groups defined for vaccination: A cross-sectional study in Araba/Alava, Spain, before the vaccination against SARS-CoV-2. (August 2022) - Parraza-Diez, Naiara; Bermudez-Ampudia, Cristina; Cobos-Campos, Raquel; Garmendia, Ines; Orruño, Estibalitz; Ojeda, Elena; Garitano, Ignacio; Robledo, María; Portu, Jose Joaquín; Apiñaniz, Antxon
Abstract: Background: The acceptability of COVID-19 vaccine varies depending on the time, place, type of vaccine and information available at the time. Knowledge of attitudes and practices towards COVID-19 among the population at high risk of developing the disease would help to tailor the strategy to improve adherence to vaccination recommendations. Aim: To analyze the willingness, knowledge and risk perception of patients and health care workers (HCW) to get the vaccines against SARS-CoV-2. Methods: Cross-sectional survey in Araba/Álava province (Spain). Subjects who met the criteria for the influenza vaccination in 2019 and HCWS from the Basque Public Health Service were included. The participants answered a questionnaire on the knowledge, attitudes and practices towards COVID-19 before starting vaccination against SARS-CoV-2. The intention to vaccinate was compared using the chi-squared test. Results: 316 HCWs and 389 patients responded to the survey. Around 90% of the patients and 80% of HCW would accept vaccination in all scenarios according to the questionnaire (p < 0.001). Only 3–12% hesitated about the COVID-19 vaccines. Compared to 40–70% of patients, 60–80% of HCWs perceived a high risk of COVID-19 (p < 0.001). Statistically significant differences were found in 10 of the 17 questions regarding the mechanism of transmission and symptoms. Conclusion: HCWs had a better knowledge and risk perception of COVID-19 than the surveyed patients. They had a higher proportion of hesitancy to get COVID-19 vaccine, probably related to doubts about the effectiveness of the new vaccines and the scientific evidence.